Prostate cancer risk, screening and management in patients with germline BRCA1/2 mutations - Rajwa, Pawel; Quhal, Fahad; Pradere, Benjamin; Gandaglia, Giorgio; Ploussard, Guillaume; Leapman, Michael S; Gore, John L; Paradysz, Andrzej; Tilki, Derya; Merseburger, Axel S; Morgan, Todd M; Briganti, Alberto; et al. (Nature reviews. Urology, 2023)
Mutations in the BRCA1 and BRCA2 tumour suppressor genes are associated with prostate cancer risk; however, optimal screening protocols for individuals with these mutations have been a subject of debate. Several prospective studies of prostate cancer incidence and screening among BRCA1/2 mutation carriers have indicated at least a twofold to fourfold increase in prostate cancer risk among carriers of BRCA2 mutations compared with the general population. Moreover, BRCA2 mutations are associated with more aggressive, high-grade disease characteristics at diagnosis, more aggressive clinical behaviour and greater prostate cancer-specific mortality. The risk for BRCA1 mutations seems to be attenuated compared with BRCA2. Prostate-specific antigen (PSA) measurement or prostate magnetic resonance imaging (MRI) alone is an imperfect indicator of clinically significant prostate cancer; therefore, BRCA1/2 mutation carriers might benefit from refined risk stratification strategies. However, the long-term impact of prostate cancer screening is unknown, and the optimal management of BRCA1/2 carriers with prostate cancer has not been defined. Whether timely localized therapy can improve overall survival in the screened population is uncertain. Long-term results of prospective studies are awaited to confirm the optimal screening strategies and benefits of prostate cancer screening among BRCA1/2 mutation carriers, and whether these approaches ultimately have a positive impact on survival and quality of life in these patients.